Stromal Keratitis After Varicella in Children. Issue 6 (June 2020) - Denier, Margot; Gabison, Eric; Sahyoun, Marwan; Labetoulle, Marc; Dureau, Pascal; Cochereau, Isabelle; Doan, Serge
Abstract : Purpose: We describe here a case series of patients with stromal keratitis of chronic course, a potential manifestation after chickenpox in children. Methods: This is a retrospective review of 8 eyes (7 children) with stromal keratitis after varicella seen in our referral cornea center. All patients received a systemic antiviral treatment with oral acyclovir and topical steroid eye drops. Topical cyclosporine eye drops were associated with steroids in case of steroid dependence or steroid-related side effects. Both antiinflammatory treatments were slowly tapered over time. Results: Median age at diagnosis was 3 years and 4 months. Stromal keratitis was unilateral in 6 children (85.7%) and consisted of superficial nummular keratitis in 4 cases and deep stromal diffuse keratitis in 3 cases. During the median follow-up of 31 months (range, 13–59 months), 6 children had 1 to 6 episodes of relapse. The median duration of topical steroid eye drop was 26 months (range, 2–59 months). Topical cyclosporine eye drops were used with steroids in 3 patients (42.9%). Three patients stopped topical steroids after 2, 5, and 8 months, without recurrence. Four patients were still undergoing treatment after a median of 43 months (range, 26–59 months). All patients regained a best-corrected visual acuity of 20/20 at the end of the follow-up. Conclusions: Stromal keratitis after varicella is an entity with a potential chronic course lasting 3 months or more. Steroid dependence and relapses during tapering are 2 major challenges for the management.